2014
DOI: 10.1007/s00213-014-3639-6
|View full text |Cite
|
Sign up to set email alerts
|

Persistent modification of forebrain networks and metabolism in rats following adolescent exposure to a 5-HT7 receptor agonist

Abstract: Persistent MR-detectable modifications indicate a rearrangement within forebrain networks, accounting for long-lasting behavioural changes as a function of developmental 5-HT7-R stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 88 publications
6
55
2
Order By: Relevance
“…One clue is given by the fact that 5-HT7 is found to be functionally linked to forebrain limbic networks, which comprise the amygdala, VS, orbital PFC, and thalami [33]. Moreover, a recent report [56] demonstrated that serotonin acts on inhibitory interneurons in the PFC through Gs proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One clue is given by the fact that 5-HT7 is found to be functionally linked to forebrain limbic networks, which comprise the amygdala, VS, orbital PFC, and thalami [33]. Moreover, a recent report [56] demonstrated that serotonin acts on inhibitory interneurons in the PFC through Gs proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this positive effect might be explained by more complex circuits, leading - eventually - to the re-modeling of cognitive maps: in this context, recent findings [33] point to enhanced transmission between limbic networks including the hippocampus, that might explain the improved SSA (essential to build spatial maps). Furthermore, the same approach has confirmed the hypothesis that the mesocortical DA branch is, in the NHE rat model, at a higher functional state [14], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, stimulation of 5-HT7R in adolescent rats by intraperitoneal administration of LP-211 (0.25 mg/kg/day for 5 days), induces plastic rearrangements within forebrain networks, accounting for long-lasting behavioral changes in the adulthood (Canese et al, 2014). Similar results were obtained in a rat model for Attention Deficit Hyperactivity Disorder (ADHD) in which prepuberal stimulation of 5-HT7R by intraperitoneal administration of LP-211 (up to 0.5 mg/kg/day for 14 days), has long-term effects on adult behavior, improving spatial attention and resulting in modified expression of pre- and post-synaptic markers (Ruocco et al, 2014a), while the same treatment, during adolescence, modulates the emotional responses (Ruocco et al, 2014b).…”
Section: The Serotonin Receptor 7 Modulates Connectivity In Adolescenmentioning
confidence: 99%
“…Animal models suggest several possible indications of 5-HT 7 R agonists as therapeutics. The stimulation of 5-HT 7 R in adolescent rats by LP-211 causes plastic rearrangements within the forebrain networks, accounting for long-lasting behavioural changes in adulthood 34 . The activation of 5-HT 7 R was found to be beneficial in mouse models of Rett syndrome 35 and fragile X syndrome 36 .…”
Section: Introductionmentioning
confidence: 99%